Hypercrosslinked Additives for Ageless Gas‐Separation Membranes. (8th January 2016) - Lau, Cher Hon; Mulet, Xavier; Konstas, Kristina; Doherty, Cara M.; Sani, Marc‐Antoine; Separovic, Frances; Hill, Matthew R.; Wood, Colin D.
Abstract: The loss of internal pores, a process known as physical aging, inhibits the long‐term use of the most promising gas‐separation polymers. Previously we reported that a porous aromatic framework (PAF‐1) could form a remarkable nanocomposite with gas‐separation polymers to stop aging. However, PAF‐1 synthesis is very onerous both from a reagent and reaction‐condition perspective, making it difficult to scale‐up. We now reveal a highly dispersible and scalable additive based on α, α′‐dichloro‐ p ‐xylene ( p ‐DCX), that inhibits aging more effectively, and crucially almost doubles gas‐transport selectivity. These synergistic effects are related to the intimately mixed nanocomposite that is formed though the high dispersibility of p ‐DCX in the gas‐separation polymer. This reduces particle‐size effects and the internal free volume is almost unchanged over time. This study shows this inexpensive and scalable polymer additive delivers exceptional gas‐transport performance and selectivity.